2013
DOI: 10.4236/jep.2013.44040
|View full text |Cite
|
Sign up to set email alerts
|

Clusterization of Surface Water Quality and Its Relation to Climate and Land Use/Cover

Abstract: The quality of surface water is rapidly changing due to climatic variations, natural processes, and anthropogenic activities. The objectives of this study were to classify and analyze the surface water quality of 12 major rivers of Alberta on the basis of 17 parameters during the period of five years (i.e., 2004-2008) using principal component analysis (PCA), total exceedance model and clustering technique. Seven major principal components (PCs) with variability of about 89% were identified. These PCs were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…The elevated concentrations of the pollutant constituents associated with particulate solids (e.g., TURB) or attached to particulate solids (e.g., TP) in water bodies can be ascribed to their wash-off (mobilization and transport) from non-point source pollutants accumulated on land surface by surface runoff generated from precipitation. Same results were obtained in studies by Budai and Clement [39] and by Akbar et al [40] in Alberta rivers. A study by Delpla et al [27] also showed that DOC is also transported from soil to rivers during rainfall events from watersheds consisting of agricultural land.…”
Section: The Dependence Of Water Quality On Precipitationsupporting
confidence: 87%
See 1 more Smart Citation
“…The elevated concentrations of the pollutant constituents associated with particulate solids (e.g., TURB) or attached to particulate solids (e.g., TP) in water bodies can be ascribed to their wash-off (mobilization and transport) from non-point source pollutants accumulated on land surface by surface runoff generated from precipitation. Same results were obtained in studies by Budai and Clement [39] and by Akbar et al [40] in Alberta rivers. A study by Delpla et al [27] also showed that DOC is also transported from soil to rivers during rainfall events from watersheds consisting of agricultural land.…”
Section: The Dependence Of Water Quality On Precipitationsupporting
confidence: 87%
“…The land use and/or the anthropogenic interference present variation, which could result in the variations of point and non-point source contributions along a river, might explain the spatial variation of precipitation response of water quality. The impact of land use/cover on water quality of Alberta's rivers have been confirmed in the most recent studies [40,41].…”
Section: Water Quality Variation Under Different Precipitation Magnitmentioning
confidence: 76%
“…>50 NTU). The variation in the water quality for different years could be related to surface runoff from different amount of precipitations due to climatic factors like snowmelt and rainfall [6]. The impact of natural sub-regions was reflected on the river water quality classification in Tab.…”
Section: Application Of Models For Spatial and Temporal Analysismentioning
confidence: 99%
“…During the growing season, the snowmelt wash various materials from the land surface into the rivers due to anthropogenic activities related to different types of land use/cover. Turbidity was found to be a dominant parameter associated with the deterioration in water quality during the growing season . On this basis, we considered turbidity separately besides CWQI in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation